Physiological and pathological roles of PGAM5: An update and future trend - Weibin He; Wenlong He; Zhongchan Sun; Pengcheng He (iScience, 2025)
Summary: PGAM5, a phosphatase found in mitochondria, is crucial for mitochondrial quality control (MQC) through its regulation on mitochondrial dynamics, biogenesis, and mitophagy. Previous studies have shown its involvement in multiple regulated cell deaths (RCDs), including apoptosis, necroptosis, and pyroptosis. The objective of this review is to enhance our comprehension of the involvement of PGAM5 in MQC and RCDs. Additionally, we summarize some novel roles of PGAM5 in cellular senescence, lipid metabolism, and immune response modulation in recent studies. Finally, we discuss PGAM5’s contribution to the pathological state of cardiovascular, hepatic, neurological, and neoplastic diseases, offering potential perspectives for future research.